Instrumental Neutron Activation Analysis (INAA) of Cisadane Estuarine Sediments - Lubis, Ali Arman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2007)
Nuclear analytical technique instrumental neutron activation analysis was employed for the multielemental analysis of sediments collected from Cisadane estuary. This analytical technique provides concentration of 20 elementswhich consist of heavy metals and rare earth elements simultaneously. Two sediments cores were collected using core sampler for determining the distribution of all elements in the depth profiles of sediments. Sediment cores were subdivided into 2 cm increment, dried and sent to reactor for irradiation using thermal flux of ?1013 neutrons.cm-2.s-1 for 20 minutes in Research Reactor Siwabessy, National Nuclear Energy Agency (BATAN), Serpong. Irradiated samples were measured using a multichannel analyzer (MCA) gamma spectrometer coupled with high purity germanium detector. Analysis of particle size was done since uptake of heavy metals by sediments is particle-size dependent. The results are presented and discussed.